Genomic regions and candidate genes associated with seed nitrogen, phosphorus, and sulfur accumulation identified in the soybean ‘Forrest’ by ‘Williams 82’ RIL population - Nacer Bellaloui; Jiazheng Yuan; Dounya Knizia; Qijian Song; Frances Betts; Teresa Register; Earl Williams; Naoufal Lakhssassi; Hamid Mazouz; Henry T. Nguyen; Khalid Meksem; Alemu Mengistu; et al. (PLoS ONE, 2025)
Nitrogen (N), phosphorus (P), and sulfur (S) are essential nutrients for plant health. Deficiencies in N, P, or S in plants lead to lower seed production and seed quality in grain crops, including soybean seed. Soybean seed is a source of protein, oil, essential amino acids, and minerals. These nutrients are essential for plant health, and maintaining N, P, and S levels in soybean seed is crucial for higher seed nutritional value and amino acids quality. There is limited information on genomic regions, candidate genes, and molecular markers associated with soybean seed N, P, and S. Two field experiments were carried out in two locations using a ‘Forrest’ × ‘Williams 82’ recombinant inbred lines (RIL) population. A 306 RIL population and 2075 SNP markers were used to create the genetic map. The results showed a wide range of N, P, and S concentrations in both locations among RIL population lines. Based on the broad-sense heritability (H2), 91.7% of seed N concentration variation was due to genetic effects, followed by 48.2% for S seed concentration, and a heritability of close to zero for seed P concentration. Eleven QTL were identified for seed N, seven QTL for seed P, and nine QTL for seed S in two locations. All these QTL had a significant linkage to the trait as their LOD ranged from 2.5 to 6.48 in 2018 and from 2.75 to 128.72 in 2020. Two QTL for seed N (qN-02-[IL-2020] on Chr 4, and qN-03-[IL-2020] on Chr 4 were identified at the marker Gm04_4687302-Gm04_7672403 and Gm04_7672403, and their LOD were 45.06 and 96.98, and their contribution to the phenotypic variation were 45.85% and 48.37%, respectively. The low heritability of P indicated a major interactions between the trait (P) and environment. Except for the seed N, P, and S QTL, identified on Chr 16, 11 QTL reported here were not previously identified and therefore are novel. Several functional genes encoding N-, P-, and S-proteins, enzymes, and transporters were identified and located within the QTL interval. To our knowledge, the QTL identified here on Chr 2 and 6 are novel and were not previously identified. Therefore, QTL, genes, and molecular markers discovered in this research will provide breeders with new knowledge and tools for soybean selection for optimum seed mineral nutritional qualities. Also, this new findings advance our knowledge of physiology and genetics of seed N, S, and P candidate genes for genetic engineering application.